An investigation of young girls’ responses to sexualized images - Jongenelis, M.; Pettigrew, Simone; Byrne, S.; Biagioni, N. (Elsevier BV, 2016)
© 2016 Elsevier LtdEvidence suggests that the sexualization of girls has increased and become more explicit in recent years. However, most of the research conducted to date has focused on sexualization in adults. To address this research gap, this study explored how young Australian girls respond to and describe sexualized and non-sexualized depictions of their peers. Results from 42 girls aged 6–11 years revealed that sexualization was a perceptually salient attribute, with participants readily classifying sexualized girls as a subgroup. Participants also made distinct trait attributions based on the differences between sexualized and non-sexualized girls. The results suggest that young girls respond differently to sexualized and non-sexualized depictions of their peers and are beginning to develop stereotypes based on these depictions. As such, the implementation of media literacy programs in adolescence may be too late and efforts may be required to address this issue among younger children.